Implications of Constructivist Theory in Islamic Religious Education Learning in Elementary School - Jami'atul Husna; Ermis Suryana; Zulhijra Zulhijra (Journal of Educational Sciences, 2026)
Islamic Religious Education (PAI) plays an important role in shaping students’ character and spirituality. However, at SD Negeri 74 Palembang, learning has tended to remain teacher-centered, so students’ active engagement has not been optimal. This study aims to describe the implementation of constructivist theory in PAI learning on the topic of prayer in the third grade, analyze its impact on students’ understanding and religious attitudes, and identify the challenges faced by teachers within a context of limited resources. The study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data were analyzed using the interactive model of Miles and Huberman, while validity was ensured through source and technique triangulation. The findings indicate that the teacher implemented constructivist principles through prayer demonstrations, reflective discussions, direct practice, and experience-based learning. Students became more active, developed a deeper understanding of worship, and demonstrated growth in discipline, concentration in prayer, and responsibility. Despite limited school facilities, teacher creativity enabled learning to remain contextual and meaningful. Thus, the implementation of constructivist theory proved effective in creating active, reflective, and student-centered PAI learning that is relevant for application in elementary schools.